Artificial Diels–Alderase based on the transmembrane protein FhuA - Osseili, Hassan; Sauer, Daniel F.; Beckerle, Klaus; Arlt, Marcus; Himiyama, Tomoki; Polen, Tino; Onoda, Akira; Schwaneberg, Ulrich; Hayashi, Takashi; Okuda, Jun (Beilstein Journal of Organic Chemistry, 2016)
Copper(I) and copper(II) complexes were covalently linked to an engineered variant of the transmembrane protein Ferric hydroxamate uptake protein component A (FhuA ΔCVFtev). Copper(I) was incorporated using an N-heterocyclic carbene (NHC) ligand equipped with a maleimide group on the side arm at the imidazole nitrogen. Copper(II) was attached by coordination to a terpyridyl ligand. The spacer length was varied in the back of the ligand framework. These biohybrid catalysts were shown to be active in the Diels–Alder reaction of a chalcone derivative with cyclopentadiene to preferentially give the endo product.
Keywords: artificial Diels-Alderase; biohybrid catalysis; copper enyzme; membrane protein